Global capital, political institutions, and policy change in developed welfare states - Swank, Duane (Cambridge studies in comparative politics., 2002)
This book argues that the dramatic post-1970 rise in international capital mobility has not systematically contributed to the retrenchment of developed welfare states as many claim. Nor has globalization directly reduced the revenue-raising capacities of governments and undercut the political institutions that support the welfare state. Rather, institutional features of the polity and the welfare state determine the extent to which the economic and political pressures associated with globalization produce Welfare state retrenchment.